2001
DOI: 10.1002/1521-4141(2001010)31:10<2960::aid-immu2960>3.0.co;2-u
|View full text |Cite
|
Sign up to set email alerts
|

Influence of enterotoxin on mucosal intranet: selective inhibition of extrathymic T cell development in intestinal intraepithelial lymphocytes by oral exposure to heat-labile toxin

Abstract: We tested the possibility that heat‐labile enterotoxin of Escherichia coli (LT) affects the development of extrathymic T cells in the intraepithelial lymphocyte (IEL) compartment. After oral administration of LT, the number of extrathymic CD8α α+ IEL was selectively and significantly diminished when compared with the corresponding cells in phosphate‐buffered saline‐fed control mice. To clarify the mechanism behind this selective reduction of CD8α α+ IEL, we analyzed the expression of essential cytokines and th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2004
2004
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 45 publications
(52 reference statements)
0
2
0
Order By: Relevance
“…The B subunits of these toxins alone are strongly antigenic and appear to have some adjuvant action, but this effect is highly reduced from that seen for the intact holotoxin. Kim et al (15) reported that holo-LT selectively inhibits the extrathymic T-cell development of intestinal epithelial lymphocytes, including ␣␤ and ␥␦ T cells. As yet, however, no reports have demonstrated that CT, LT, or their corresponding B subunits can recruit and activate peritoneal ␥␦ T cells.…”
Section: Discussionmentioning
confidence: 99%
“…The B subunits of these toxins alone are strongly antigenic and appear to have some adjuvant action, but this effect is highly reduced from that seen for the intact holotoxin. Kim et al (15) reported that holo-LT selectively inhibits the extrathymic T-cell development of intestinal epithelial lymphocytes, including ␣␤ and ␥␦ T cells. As yet, however, no reports have demonstrated that CT, LT, or their corresponding B subunits can recruit and activate peritoneal ␥␦ T cells.…”
Section: Discussionmentioning
confidence: 99%
“…Overexpression of MHC class Irelated chain A in the intestine of experimental transgenic mice resulted in a clonal expansion of CD4 + CD8 + IELs and attenuated acute colitis in an experimental model of inflammatory bowel disease induced by dextran sodium sulfate administration (Park et al, 2003). CD8 + IELs developed along an extrathymic pathway may work as antiinflammatory regulator T cells to sustain the mucosal intranet formed by intestinal epithelial cells and IELs and to diminish the expansion of enterotoxigenic Escherichia coli (Kim et al, 2001). Although ingesting SpHW did not significantly increase the level of CD4 + CD8 + IELs in the present study, these facts, in addition to our present results, suggest that ingestion of Spirulina appears to be effective for protecting immune functions or improving immune systems vulnerable to age, thereby reducing the risk of infectious and autoimmune diseases.…”
Section: Characterization Of Iels Of Adult and Aged Micementioning
confidence: 99%